2011
DOI: 10.1007/s12199-011-0244-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health-promoting lifestyle profile in Japanese university students

Abstract: These significant findings linking the HPLP-II, university year level, and living with family (yes/no) in university students will enable healthcare providers to develop interventions to assist students in improving their health lifestyles in the university environment and will help in devising suitable education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
133
4
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(183 citation statements)
references
References 15 publications
33
133
4
13
Order By: Relevance
“…(3) Data pointing out that college students who live with their families had better nutritional habits have also been found, and that those enrolled in the first year of college tend to present improved health behaviors when compared with students in subsequent periods. (15) As for the overweight, this study observed a higher percentage of cases in comparison with the findings among American university students. The causes for the overweight and obesity were the eating disorders and lack of physical activity during the academic life.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…(3) Data pointing out that college students who live with their families had better nutritional habits have also been found, and that those enrolled in the first year of college tend to present improved health behaviors when compared with students in subsequent periods. (15) As for the overweight, this study observed a higher percentage of cases in comparison with the findings among American university students. The causes for the overweight and obesity were the eating disorders and lack of physical activity during the academic life.…”
Section: Discussionsupporting
confidence: 40%
“…Such findings agree with other studies in which female participants were found more likely to have healthier eating habits and lower interest for physical activities. (5,15) A research with Spanish college students showed that women were less active and had a more sedentary lifestyle than men and therefore the realization of specific intervention actions for women was recommended. (3) Data pointing out that college students who live with their families had better nutritional habits have also been found, and that those enrolled in the first year of college tend to present improved health behaviors when compared with students in subsequent periods.…”
Section: Discussionmentioning
confidence: 99%
“…This means that health promoting life-style behaviour can reach up to this level of awareness depending on the cultural and economical status. In studies performed in the USA with working women (Duffy et al, 1996), in Taiwan with pregnant women (Lin et al, 2009), in Japan workers (Zhang et al, 2011), in Japanese university students (Wei et al, 2012) and in Jordan with the Arabian Muslims (Al Ma'aitah et al, 1999), similar results were found.…”
Section: Discussionmentioning
confidence: 57%
“…Hong et al reported among undergraduate nursing students at Mahidol University in Turkey, a medium overall HPLP II mean score in more than half the students, with the best performance in interpersonal relations, and the worst in physical exercise (23). Wei et al revealed among Japanese university students a medium overall HPLP II mean score with the highest score for interpersonal relations and the lowest for health responsibility (29). Some of the studies revealed a non-healthy lifestyle among university students.…”
Section: Discussionmentioning
confidence: 99%
“…In the health responsibility subscale, a low score was observed in numerous studies. This might be due to the fact that students have good health at that age and do not perceive responsibility for health as something that requires extra attention (21,23,28,29,31). In concordance with this, Wolf et al observed among college students in United States (USA) a decline in interest for medical examination at the end of the academic year, compared to the beginning (21).…”
Section: Discussionmentioning
confidence: 99%